2018
DOI: 10.1016/j.drugpo.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Safe and unsafe spaces: Non-fatal overdose, arrest, and receptive syringe sharing among people who inject drugs in public and semi-public spaces in Baltimore City

Abstract: The spaces in which drug use occurs constitutes a key aspect of the "risk environment" of people who inject drugs (PWID). We aimed to add nuance to the characterization of "safe" and "unsafe" spaces in PWID's environments to further understand how these spaces amplify the risk of morbidities associated with injection drug use. PWID were recruited through the Baltimore City syringe service program and through peer referral. Participants completed a socio-behavioral survey. Multivariable logistic regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…Finally, we observed that non-fatal overdose was higher among homeless PWID compared to PWID with stable housing, speaking to the importance of attending to the structural vulnerability of this population and their direct impacts on overdose [ 12 , 30 ]. We found that homelessness was also strongly associated with public injecting (e.g., injecting on the street or in a public bathroom), an association that we have examined further [ 31 ]. It is known that homelessness is associated with a range of negative health outcomes among PWID including injection risk behaviors [ 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed that non-fatal overdose was higher among homeless PWID compared to PWID with stable housing, speaking to the importance of attending to the structural vulnerability of this population and their direct impacts on overdose [ 12 , 30 ]. We found that homelessness was also strongly associated with public injecting (e.g., injecting on the street or in a public bathroom), an association that we have examined further [ 31 ]. It is known that homelessness is associated with a range of negative health outcomes among PWID including injection risk behaviors [ 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey ascertained sociodemographic data (age, race, gender, employment and housing status), current substance use, including recent (past 6 months) illicit fentanyl use and preference, habits surrounding use (route of administration, drug use setting) and overdose history. Questions were adapted from previous work . Employment was defined as full or part‐time employment, excluding illicit income‐generation which pays ‘under the table’ or ‘off the books’, and involvement in the drug or sex trade.…”
Section: Methodsmentioning
confidence: 99%
“…The survey also included items on rushing drug purchases, preparation or use due to policing (past year), settings where drugs were usually used (past 30 days), and using drugs alone. Drug use setting [26] was modeled after our previous work: public spaces for drug use were defined as using in a street or park; semi-public spaces were defined as building stairwells, abandoned buildings, public restrooms, in a vehicle, and at a shooting gallery; and private spaces were in the participant's home or somebody else's home. The survey ascertained any access to a variety of health services in the past 6 months (emergency room, drug treatment, health care provider, and SSP), whether they currently had naloxone, and interest in using fentanyl test strips (FTS).…”
Section: Methodsmentioning
confidence: 99%